Quality of Life in the Swedish General Population During COVID-19 - Based on pre- and post-pandemic outbreak measurement - Sara Olofsson; Ulf Persson; Ning Yan Gu; Cynthia L. Gong; Xiayu Jiao; Joel W. Hay (University of Oslo, 2021)
The outbreak of the pandemic COVID-19 (Coronavirus) has resulted in various international and national strategies, including non-pharmaceutical interventions (NPIs) such as social distancing and travel bans, which have purportedly mitigated the health loss due to the pandemic but also given rise to a severe economic crisis. Both factors, the pandemic and the NPIs, can be expected to have an impact on the Health-Related Quality-of-Life (HRQoL) of the population. The objective of this study was to estimate the impact on HRQoL of the Swedish adult population during the outbreak of the COVID-19 pandemic. A web-based survey was sent to randomised samples of the adult Swedish population before the outbreak of the pandemic in Sweden in February 2020 (n=1,016) and during the outbreak of the pandemic. The first wave pandemic data was collected in April 2020 (n=1,003), one-month after the outbreak and, the second wave data was collected in January 2021 (n=1,013), after 10-months living under the pandemic. HRQoL was measured using the EQ-5D-5L in the pandemic surveys, whereas the Visual Analogue Scale (VAS) was used in all surveys. The results suggested a reduction in average HRQoL as measured by VAS in the adult Swedish population, with 0.059 points reduction in VAS in April 2020 and 0.074 points reduction in January 2021, compared to the pre-pandemic measurement in February 2020.  The loss in HRQoL was significant among respondents in the working age population (<65 years), suggesting that the social and economic impact of NPIs were the primary drivers for this specific cohort. Findings of this study supports a wide public health perspective and future HRQoL measurements at the population level throughout the pandemic. Published: Online September 2021